Translokering av vedlevande mossor som ekologisk kompensation : hur reagerar de på kort sikt? - Holm, Elina (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2022)
Deadwood is an important component driving biodiversity in forest ecosystems. Of the 300 forest living bryophytes in Sweden, one third occur on deadwood. When the copper mine Aitik in Gällivare, Sweden expanded their sand magazine, an area with old forest that hosted very high natural values was removed. To compensate for the loss of natural values, the Land and Environmental Court of Sweden ordered Boliden to perform ecological compensation, which is a method used to counteract loss of biodiversity and ecosystem services. As a part of the compensation over 600 logs containing species of bryophytes, lichens, insects, and fungi associated with deadwood were removed from the impact area to a compensation area. In this study, data from two bryophyte inventories (2018 and 2021) were analyzed statistically, to investigate how the coverage and species richness of the bryophytes on the relocated logs have responded in short term, and if there were any differences in coverage and species richness on logs of pine and spruce. The results showed significant increases in coverage and species richness between the years, but no significant differences between logs of pine and spruce. It’s hard to evaluate how the relocation has affected bryophytes since the period between the inventories is relatively short and because this study doesn’t show how individual species (e. g. threatened obligate species) has been affected by the relocation. More research is needed in the area and when ecological compensation is used as a tool its effects should last long-term and need to be compared with the losses of biodiversity and ecosystem services due to the exploitation.